RETRACTED: Biomathematical approach determination of a rational formula of complex phytocompositions - Lokarev Alexander; Matveeva Irina; Markova Evgenia; Gryn Svetlana; Zaberezhny Alexey; Lyulkova Larisa; Skotnikova Tatyana; Neminushchaya Larisa; Frolova Marina; Vasiliev Stepan (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001